2017
DOI: 10.1080/0167482x.2017.1338265
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual syndrome in university students: its correlation with their attitudes toward gender roles

Abstract: GRA and sociodemographic characteristics should be considered in healthcare services for PMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
4
6
0
1
Order By: Relevance
“…Regardless of severity, the ten symptoms most often occurring among the participants include: skin disorders, irritability, fatigue, mood swings, general aches and pains, lowered school or work performance, backache, painful breasts, weight gain, and swelling. The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30].…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of severity, the ten symptoms most often occurring among the participants include: skin disorders, irritability, fatigue, mood swings, general aches and pains, lowered school or work performance, backache, painful breasts, weight gain, and swelling. The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30].…”
Section: Discussionsupporting
confidence: 92%
“…According to the participants’ MSQ mean scores, they had more premenstrual and menstrual pain. Parallel to the current study results, similar findings have been reported in many studies . In the study with nursing students in Taiwan, Chen found that premenstrual symptoms most commonly experienced by students were mood swings, pain, and gastrointestinal disturbances.…”
Section: Discussionsupporting
confidence: 91%
“…Seven et al 32 and Karout et al 6 found that majority of nursing students were experiencing pain during menstruation. Temel et al 41 in their study with college students found that depressive thoughts, bloating symptoms were prevalent before menstruation. Furthermore, studies investigating the relationship between PMS and depression suggest that PMS may create a predisposal to depression.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations